A study of nanoparticles as a drug carrier on the wall of Stenosed Arteries - Jamil, Dzuliana Fatin; Sufahani, Suliadi Firdaus; Kamardan, Muhamad Ghazali; Abdulhameed, Mohammed; Hashim, I.; Roslan, Rozaini (Pushpa Publishing House, 2018)
The influences of nanoparticles as drug carriers on the walls of stenosed arteries are presented. In this study, three nanoparticles namely Fe3O4 , TiO2 and Cu were used. It is observed that the addition of Fe3O4 nanoparticles tends to reduce the resistance impedance of blood temperature in bell shaped stenosed arteries. The blood temperature increases slightly in the streamwise direction before the throat region. Thereafter, the blood temperature increases at a higher rate and reaches its maximum value at the stenosis throat. It is found that the temperature distribution is heavily dependent on parameters such as periodic body acceleration and Prandtl number.